Implementing a systems-oriented morbidity and mortality conference in remote rural Nepal for quality improvement. Issue 12 (26th September 2011) - Schwarz, Dan; Schwarz, Ryan; Gauchan, Bikash; Andrews, Jason; Sharma, Ranju; Karelas, Gregory; Rajbhandari, Ruma; Acharya, Bibhav; Mate, Kedar; Bista, Amir; Bista, Megha Giri; Sox, Colin; et al.
Abstract : Problem: In hospitals in rural, resource-limited settings, there is an acute need for simple, practical strategies to improve healthcare quality. Setting: A district hospital in remote western Nepal. Key measures for improvement: To provide a mechanism for systems-level reflection so that staff can identify targets for quality improvement in healthcare delivery. Strategies for change: To develop a morbidity and mortality conference (M&M) quality improvement initiative that aims to facilitate structured analysis of patient care and identify barriers to providing quality care, which can subsequently be improved. Design: The authors designed an M&M involving clinical and non-clinical staff in conducting root-cause analyses of healthcare delivery at their hospital. Weekly conferences focus on seven domains of causal analysis: operations, supply chain, equipment, personnel, outreach, societal, and structural. Each conference focuses on assessing the care provided, and identifying ways in which services can be improved in the future. Effects of change: Staff reception of the M&Ms was positive. In these M&Ms, staff identified problem areas in healthcare delivery and steps for improvement. Subsequently, changes were made in hospital workflow, supply procurement, and on-site training. Lessons learnt: While widely practiced throughout the world, M&Ms typically do not involve both clinical and non-clinical staff members and do not take a systems-level approach. The authors' experience suggests that the adapted M&M conference is a simple, feasible tool for quality improvement in resource-limited settings. Senior managerial commitment is crucial to ensure successful implementation of M&Ms, given the challenging logistics of implementing these programmes in resource-limited health facilities.